Impact of User-Generated Content on Purchase Intention for Fashion Products:A Study on Women Consumers in Bangalore - Venkataraman, Nithya; Raman, Sreedhara (Indian Journal of Marketing, 2016)
The advent of online media has been instrumental in providing consumers with quick, relevant, and convenient information on products and services. The success of such media has been established for businesses such as tourism, automobile, and consumer electronics- wherein consumers tend to decide on final purchases based on user - generated content (UGC) such as customer reviews and feedback rather than on traditional advertising media. With short lead times, quick turnaround of products, and frequent changes in offerings, the fashion industry is also exploring the use of such user-generated content for marketing its products. This study sought to explore and understand the relevant factors that draw consumers towards the usage of user-generated content (UGC) in the online space for the fashion business, and its impact on the purchase intention for different categories of fashion products. The study focused on the cosmopolitan city of Bengaluru, known for its fashion centricity and brand awareness. It attempted to analyze the factors for reference to media content generated by co-consumers, especially amongst women, and inferred that content that provides them with gratifications relating to social acceptance are more liable to positively influence their intent to purchase. It also specifically identified product categories that are liable to benefit from such content.